Teknik Simulasi Media Whatsapp untuk Meningkatkan Etika Berkomunikasi Mahasiswa dengan Dosen - Syarifah Ainy Rambe; Husrin Konadi (Jurnal SOMASI (Sosial Humaniora Komunikasi), 2020)
This study aims to improve students' communication ethics with lecturers through Whatsapp media with simulation techniques. This study uses the Classroom Action Research (CAR) method, using two cycles and consisting of 4 stages, namely planning, action, observation and reflection. The sampling technique in this study used purposive sampling, where the sample was taken based on the needs and specific objectives of this study, so that the sample that was daimbil was the 7th semester students of the PIAUD si STAIN Gajah Putih Takengon study program, totaling 27 people. The results of this study indicate an increase in student ethics in communicating with lecturers through Whatsapp media using whatsapp media in presiklus, cycle 1 and cycle 2.